The Influence of Instagram Social Media Marketing Activities of Somethinc on Customer Purchase Intention - Kiki Anggraini; Anas Hidayat (International Journal of Economics, Business and Innovation Research, 2024)
Technological advancements have seen significant growth, encompassing various aspects of life, including the buying and selling of products. The advent of the internet has given rise to numerous digital social media platforms that are now widely utilized by entrepreneurs to conduct product transactions. As market competition intensifies, entrepreneurs need to implement efficient and easily executable marketing strategies to remain relevant among competitors. This study aims to analyze the influence of social media marketing activity on the purchase intention of the skincare brand Somethinc. The focus of this research is on the social media marketing activities of the skincare brand Somethinc conducted on the Instagram platform. This research was carried out by distributing questionnaires via Google Forms, which were then disseminated through the researchers' social media. Convenience sampling was used in this study, with a total of 250 respondents. The obtained data were analyzed using quantitative methods and processed using SPSS and Smart PLS applications. The results showed that social media marketing activities positively influenced brand awareness and brand image. Brand awareness also had a positive effect on electronic word of mouth, and brand image positively influenced electronic word of mouth. Finally, electronic word of mouth also had a positive effect on purchase intention. The findings of this study are expected to assist entrepreneurs in designing effective marketing strategies, enabling them to compete with other competitors in marketing through social media, particularly Instagram.